Comparative analysis of organellar genomes between diploid and tetraploid Chrysanthemum indicum with its relatives - Liu, Huihui; Hou, Zhuangwei; Xu, Lei; Ma, Qing; Wei, Min; Tembrock, Luke R.; Zhang, Shuo; Wu, Zhiqiang (Frontiers in Plant Science, 2023)
Chrysanthemum indicum, a species native to Eastern Asia is well known as one of the progenitor species of the cultivated Chrysanthemum which is grown for its ornamental and medicinal value. Previous genomic studies on Chrysanthemum have largely ignored the dynamics of plastid genome (plastome) and mitochondria genome (mitogenome) evolution when analyzing this plant lineage. In this study, we sequenced and assembled the plastomes and mitogenomes of diploid and tetraploid C. indicum as well as the morphologically divergent variety C. indicum var. aromaticum. We used published data from 27 species with both plastome and mitogenome complete sequences to explore differences in sequence evolution between the organellar genomes. The size and structure of organellar genome between diploid and tetraploid C. indicum were generally similar but the tetraploid C. indicum and C. indicum var. aromaticum were found to contain unique sequences in the mitogenomes which also contained previously undescribed open reading frames (ORFs). Across Chrysanthemum mitogenome structure varied greatly but sequences transferred from plastomes in to the mitogenomes were conserved. Finally, differences observed between mitogenome and plastome gene trees may be the result of the difference in the rate of sequence evolution between genes in these two genomes. In total the findings presented here greatly expand the resources for studying Chrysanthemum organellar genome evolution with possible applications to conservation, breeding, and gene banking in the future.